SOCIALIZATION URGENCY OF LEGAL PROTECTION OF INTELLECTUAL PROPERTY RIGHTS FOR VILLAGE IN LEGISLATIVE DRAFTING PURPOSE - ADHITYA WIDYA KARTIKA; SUTRISNO SUTRISNO (UNTAG Law Review, 2020)
Norms or rules are a code of conduct for human life including legal norms that are strict and direct sanctions. One of the legal products made by legislative drafters is regeling, for example laws that are made, discussed, and agreed upon between the Presidentand the House of Representatives. Legislation must be made to have a purpose. This has the understanding that a statutory regulation is a joint goal between the Government and the people represented by the House of Representatives. Another aspect is that regulations are expected to be effective. In connection with norms in the constitution referred to as the rule of law, this means that all forms of community and government behavior must be in accordance with and must not violate the laws and regulations. One of the rule of law in Indonesia is that the actions of the government must be in accordance with the laws and regulations. If we look at research in villages in SekaranSubdistrict, there are resources and potentials at a local scale that can be increased to increase village empowerment and economy. On the other side, there are laws and regulations related to this matter. This happens due to lack of socialization related to the regulation (village and intellectual property rights) so that the implementation cannot be carried out optimally. So the socialization of a regulation so as to increase the realization of the purpose of the regulation is made important. This research uses descriptive analytical method.